DIGITAL TECHNOLOGIES AS A MEANS OF ADAPTIVE LEARNING FOR HIGHER EDUCATION INFORMATICS AND MATHEMATICS - Kosovets, Olena; Soia, Olena; Krupskyi, Yaroslav; Tyutyun, Lyubov (Physical and Mathematical Education, 2022)
Formulation of the problem. In the context of online / blended learning, the relevance of research on the use of digital technologies as a means of adaptive learning for higher education in computer science and mathematics is undeniable. Implementation of the principles of adaptive learning with the help of digital technologies provides significant opportunities for individualization and differentiation of the educational process by the cognitive characteristics and educational needs of each graduate. Materials and Methods. The study is based on the work of domestic and foreign scientists. Theoretical and practical methods are used. Using the methods of system analysis and theoretical generalization a study of the implementation of adaptive learning in distance learning at Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University. Results. It is substantiated that with the development of e-learning it became possible to effectively ensure the adaptability of the learning process of higher education in computer science and mathematics. Adaptation involves the analysis of individual characteristics and the initial level of training of students, the implementation of the process of interactive learning, evaluation of success criteria for the transition to the next level of education, and more. Methodical aspects of adaptive learning in the information educational system of a higher education institution are considered. Conclusions. The system of adaptive teaching of mathematics and computer science provides the optimal adaptation of the educational process to individual characteristics and personal preferences of students, promotes their cognitive activity, increases motivation to learn, provides monitoring of learning, and adjusts it to achieve planned individual results. The adaptive learning system has the potential to ensure the full involvement of students in the process of building their individual educational trajectory, developing their activities, improving the individualization of the educational process, and more.